Perspektif Orang Tua Mengenai Intervensi Aktivitas Fisik dan Diet pada Siswa Obesitas di Sekolah Dasar - Eman, Semuel Johan; Ratag, Gustaaf A. E.; Sapulete, Margareth R. (UNIVERSITAS SAM RATULANGI, 2016)
The prevalence of obesity in children in the world is increasing every year . Overall 10 % of school-age children in the world are obese . Obesity in elementary school children in Indonesia also showed a high rate , it was found that children aged 6-14 years 9.5 % males and 6.4 % of women are obese . Therefore , the intervention of the parents is the right choice . This study aimed to determine parental perspective about physical activity and dietary interventions on obesity in elementary school students .The design of this study is Sequential Explanatory of Mixed Method. This research is descriptive study. The results showed that knowledge of informants is still lacking because the informant is still not fully understood on the definition of obesity, the characteristics of children who are obese and the impact of obesity on the health of children. Most informants felt no problem seeing their children who are obese. Action informant intervention in physical activity and diet is good but needs to be improved.